Faktor Sosial dan Budaya yang Mempengaruhi Obesitas : (Studi Kualitatif pada Wanita Usia Subur di Wilayah Kerja Puskesmas Simpang Raya Kabupaten Banggai Provinsi Sulawesi Tengah) - Salma Bahsoan; Arlin Adam; Andi Alim (Quantum Wellness : Jurnal Ilmu Kesehatan, 2025)
Obesity in women of childbearing age is a growing health problem, not only due to dietary patterns and lack of physical activity, but also due to the influence of social and cultural factors. This study aims to gain a deeper understanding of the experiences, perspectives, and habits of women of reproductive age who are obese within the context of local social and cultural norms. Using a qualitative phenomenological approach, data was collected through in-depth interviews with five primary informants who are obese, as well as triangulation informants from community health workers and healthcare professionals. The results of the study indicate that perceptions of obesity are still predominantly viewed from the perspective of physical appearance rather than health. Social factors such as family eating patterns, snacking habits, comments from others, and lack of physical activity are triggers for obesity. Meanwhile, local culture has a varied influence—some communities are beginning to adopt slim body ideals, while others remain neutral. Obesity also impacts self-confidence, social stigma, and limitations in daily activities. However, most informants expressed hope for a healthier life. This study recommends interventions that consider local cultural values and involve family and community support in obesity prevention effort.